Assessment of passive drag in swimming by numerical simulation and analytical procedure - Barbosa, Tiago M. (2020)
The aim was to compare the passive drag-gliding underwater by a numerical simulation and an analytical procedure. An Olympic swimmer was scanned by computer tomography and modelled gliding at a 0.75-m depth in the streamlined position. Steady-state computer fluid dynamics (CFD) analyses were performed on Fluent. A set of analytical procedures was selected concurrently. Friction drag (Df), pressure drag (Dpr), total passive drag force (Df+pr) and drag coefficient (CD) were computed between 1.3 and 2.5 m · s-1 by both techniques. Df+pr ranged from 45.44 to 144.06 N with CFD, from 46.03 to 167.06 N with the analytical procedure (differences: from 1.28% to 13.77%). CD ranged between 0.698 and 0.622 by CFD, 0.657 and 0.644 by analytical procedures (differences: 0.40-6.30%). Linear regression models showed a very high association for Df+pr plotted in absolute values (R2 = 0.98) and after log-log transformation (R2 = 0.99). The CD also obtained a very high adjustment for both absolute (R2 = 0.97) and log-log plots (R2 = 0.97). The bias for the Df+pr was 8.37 N and 0.076 N after logarithmic transformation. Df represented between 15.97% and 18.82% of the Df+pr by the CFD, 14.66% and 16.21% by the analytical procedures. Therefore, despite the bias, analytical procedures offer a feasible way of gathering insight on one's hydrodynamics characteristics.